The Effects of Loose Parts Play Activity Provision on Relationship Skill of Young Children - Theeranthananon, Thanunya; Hirunchalothorn, Piyanan; Lehmongkol, Pattamavadi (Journal of Inclusive and Innovative Education, 2023)
The objective of this study was to study the effects of loose parts play activity provision on relationship skill of young children. The subject were 24 boys and girls age between 3-4 years old studying in kindergarten level 1 in the second semester of academic year 2022, Ramkhamhaeng University Demonstration School (Elementary Department) under the Ministry of Higher Education, Science, Research and Innovation.The tools used in the study were 1)12 plans of loose parts plays activity in free time periods and 2) observation form of relationship skill behaviors for young children. Quantitative data were analyzed by mean and standard deviation, qualitative data were analyzed by content analysis. The study found that young children had the relationship skill mean scores before receiving loose parts plays activity was 22.71 and the standard deviation was 4.18. And after receiving the activity, the mean scores was 33.75 and the standard deviation was 2.66. In other words, young children had higher relationship skills than before the loose parts plays activity.The aspect with the highest mean scores child-child relationship skills was 16.92 and the standard deviation was 1.28 and child-adult relationship skills was 16.83 and the standard deviation was 1.46 respectively